2021
DOI: 10.3390/socsci10030108
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy Beliefs and Acceptance of COVID-Vaccine: An Exploratory Study in Italy

Abstract: The availability of vaccines does not mean that people will be willing to get vaccinated. For example, different conspiracy beliefs on the adverse effects of vaccines may lead people to avoid collective health measures. This paper explores the role played by antecedents of COVID-related conspiracy beliefs, such as the role of political ideology and the endorsement of moral purity values, and the consequences of COVID-related conspiracy beliefs in terms of the acceptance of a COVID vaccine (when available) via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 98 publications
8
59
0
1
Order By: Relevance
“…While some studies explored public compliance with health-related guidance during the COVID-19 pandemic (e.g., , or the relationship between conspiracy beliefs and support for COVID-19 vaccines (e.g., Bertin et al, 2020), this study provided a conceptual replication of the study by Pivetti et al (2021) in a novel context, in Finland, in an effort to expand current knowledge on COVID-19 vaccine hesitancy across countries and cultures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While some studies explored public compliance with health-related guidance during the COVID-19 pandemic (e.g., , or the relationship between conspiracy beliefs and support for COVID-19 vaccines (e.g., Bertin et al, 2020), this study provided a conceptual replication of the study by Pivetti et al (2021) in a novel context, in Finland, in an effort to expand current knowledge on COVID-19 vaccine hesitancy across countries and cultures.…”
Section: Discussionmentioning
confidence: 98%
“…Results showed that the attitudes toward the vaccines mediated the relationship between COVID conspiracy beliefs and attitudes toward the COVID-19 vaccine. In the current study, we aimed to conceptually replicate the study by Pivetti et al (2021) to confirm prior hypotheses, using established measures and analytical models (Morrison et al, 2010;Stroebe & Strack, 2014;Troyer et al, 2019), drawing together existing findings on the antecedents and consequences of conspiracy beliefs in a comprehensive model. Furthermore, extending Pivetti et al's work (2021), the relationships between variables of interest were examined in a new setting, that is Finland.…”
Section: Introductionmentioning
confidence: 87%
“…Some of them were carried out at a time when a vaccine was a distant solution, and others during the vaccination campaigns in individual countries. They were conducted in Poland [1,2], the United States [3][4][5][6][7], Ireland and the United Kingdom [8,9], Australia [10], Canada [11], France [12], Italy [13][14][15], Portugal [16], Finland [17], Greece [18], China [19,20] and Japan [21]. As a result of multicentre cooperation, surveys in seven European countries [22], seven European countries and the United States [23], three Asian and five African countries [24], 23 Arab countries and territories [25] and 19 countries with a high COVID-19 burden [26] have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the above-mentioned studies indicated that males [2,10,12,20,21,24], older individuals [13,14,16,18], those with a higher income and/or education level [11,12,14,16,24,29] or 2 of 13 those having been vaccinated against the flu previously [13,18,20,25,27] were more likely to accept a COVID-19 vaccine. The influence of many other factors, such as higher trust in government decisions [10,28], faith in science [15,28], political beliefs [4,5,7], perceived effectiveness of a COVID-19 vaccine [4,20], personally knowing someone who was infected by COVID-19 [12], living in a region with higher rates of COVID-19 infections [25], and living in smaller communities [13] were associated with a higher willingness to be vaccinated. Factors associated with lower willingness to be vaccinated included conspiracy beliefs [2,8,15], being unemployed [6], having suffered financial consequences during COVID-19 pandemic [11] or living in disadvantaged areas [10].…”
Section: Introductionmentioning
confidence: 99%
“…Conspiracy beliefs have been shown to be negatively associated with COVID-19 vaccination intention, according to studies conducted in France [ 22 ], the UK [ 23 ], Italy [ 24 ], and other countries, including Ireland, Spain, the US, and Mexico [ 25 ]. The underlying psychological mechanism for this conspiracy-induced vaccination skepticism could be mediated by political powerlessness [ 21 ].…”
Section: Introductionmentioning
confidence: 99%